THE COMMUNITY DEVELOPMENT AND LEPROSY SELF-CARE GROUPS IN A FIRST-LEVEL OF HEALTH FACILITIES - Suriyani Tan; Rina Kusumaratna (CV. Multi Kreasi Media, 2022)
Neglected Tropical Diseases (NTDs) remain a public health problem in 149 tropical and subtropical countries, including Indonesia. NTDs are closely related to poverty and low levels of hygiene and sanitation. In Indonesia alone, there are more than 5 types of neglected tropical diseases, one of which is leprosy. Leprosy, also known as Morbus Hansen, caused by the bacterium Mycobacterium leprae, is a disease with a long history. Leprosy can be found in several scriptures and has been known since the time of Ancient Egypt around 2000 years BC. This disease is often considered a curse on the sufferer and until now this stigma continues to stick to the sufferer. Stigmatization and social discrimination in leprosy patients make leprosy sufferers isolated from the surrounding community so that the outreach process by health workers becomes difficult. Guidance for leprosy patients in the form of counseling was carried out before the pandemic through self-care groups for leprosy sufferers, and evaluations were carried out after the pandemic to assess improvements in literacy levels and understanding of the group members. The result of this community is an increase in literacy about the adoption of water, sanitation, and hygiene (WASH) among the members of self-care groups in first-level of health facilities.